2011
DOI: 10.1100/2011/157150
|View full text |Cite
|
Sign up to set email alerts
|

The Limbic System Conception and Its Historical Evolution

Abstract: Throughout the centuries, scientific observers have endeavoured to extend their knowledge of the interrelationships between the brain and its regulatory control of human emotions and behaviour. Since the time of physicians such as Aristotle and Galen and the more recent observations of clinicians and neuropathologists such as Broca, Papez, and McLean, the field of affective neuroscience has matured to become the province of neuroscientists, neuropsychologists, neurologists, and psychiatrists. It is accepted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 55 publications
(122 reference statements)
1
83
0
4
Order By: Relevance
“…This complex also incorporates the neural network of the mesolimbic reward center,the network most involved in addiction (Roxo, Franceschini, Zubaran, Kleber, & Sander, 2011). Neuroimaging has demonstrated that viewing images of sexually available partners (i.e., pornography) has the same effect on the medial preoptic area as viewing actual sexual partners.…”
Section: Introductionmentioning
confidence: 99%
“…This complex also incorporates the neural network of the mesolimbic reward center,the network most involved in addiction (Roxo, Franceschini, Zubaran, Kleber, & Sander, 2011). Neuroimaging has demonstrated that viewing images of sexually available partners (i.e., pornography) has the same effect on the medial preoptic area as viewing actual sexual partners.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many of the structures we find in the WM network are limbic. We consider that since the concept, characterization, and delimitation of the limbic system has been controversial throughout history [LeDoux, 1991;Kötter and Meyer, 1992;Roxo et al, 2011], it does not seem appropriate to use this term to label the network. In any case, we found the proposal for labeling the networks of Hutchison et al [2011] and Ghahremani et al [2017] to be closer to what was found in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Pierre Paul Broca (1824-1880) provided compelling evidence for the concept of "localization of function," which holds that different parts of the brain do different things (24). In 1861 Dr. Broca encountered two patients.…”
Section: The Brain Function and Its Mapsmentioning
confidence: 99%